Thinking over the city at different scales: A theoretical balance for the Peruvian urban question from “Jauja Monumental” - Correa, Omar (2019)
How to ponder ‘the city’ in Peru outside of Lima? This article discusses two theoretical approaches to be taken into account in the study of intermediate cities, from the case of "Jauja Monumental": urban project which consisted in a revalorization of the architectural heritage existing at the monumental zone of this Andean city. From this case, I explore and discuss two theoretical approaches, which allow to apprehend and analyze the case with sufficient deepness and flexibility. These are, in the first place, the proposal of the "production of space" (PdE), coming from Lefebvre and the Marxist tradition. As, in the second place, the Latin American proposal of the "imaginarios urbanos" (IU) from authors such Hiernaux, Silva and Lindón. In this way, the current article aims to feed the theoretical debate on cities in Peru, from a proposal that addresses the economic-political, but also cultural and symbolic factors through which cities beyond metropolitan Lima are (re) configured over time.